A novel machine learning model and a public online prediction platform for prediction of post-ERCP-cholecystitis (PEC). (June 2022) - Zhang, Xu; Yue, Ping; Zhang, Jinduo; Yang, Man; Chen, Jinhua; Zhang, Bowen; Luo, Wei; Wang, Mingyuan; Da, Zijian; Lin, Yanyan; Zhou, Wence; Zhang, Lei; et al.
Summary: Background: Endoscopic retrograde cholangiopancreatography (ERCP) is an established treatment for common bile duct (CBD) stones. Post- ERCP cholecystitis (PEC) is a known complication of such procedure and there are no effective models and clinical applicable tools for PEC prediction. Methods: A random forest (RF) machine learning model was developed to predict PEC. Eligible patients at The First Hospital of Lanzhou University in China with common bile duct (CBD) stones and gallbladders in-situ were enrolled from 2010 to 2019. Logistic regression analysis was used to compare the predictive discrimination and accuracy values based on receiver operation characteristics (ROC) curve and decision and clinical impact curve. The RF model was further validated by another 117 patients. This study was registered with ClinicalTrials.gov, NCT04234126. Findings: A total of 1117 patients were enrolled (90 PEC, 8.06%) to build the predictive model for PEC. The RF method identified white blood cell (WBC) count, endoscopic papillary balloon dilatation (EPBD), increase in WBC, residual CBD stones after ERCP, serum amylase levels, and mechanical lithotripsy as the top six predictive factors and has a sensitivity of 0.822, specificity of 0.853 and accuracy of 0.855, with the area under curve (AUC) value of 0.890. A separate logistic regression prediction model was built with sensitivity, specificity, and AUC of 0.811, 0.791, and 0.864, respectively. An additional 117 patients (11 PEC, 9.40%) were used to validate the RF model, with an AUC of 0.889 compared to an AUC of 0.884 with the logistic regression model. Interpretation: The results suggest that the proposed RF model based on the top six PEC risk factors could be a promising tool to predict the occurrence of PEC. Funding: This work was supported by National Natural Science Foundation of China (8187103130; 32160255); Gansu Competitive Foundation Projects for Technology Development and Innovation (1602FKDA001); Gansu Province Science and Technology Planning Project (20YF8WA085); Science and Technology Planning Project of Chengguan District in Lanzhou (2020JSCX0043). The Foundation of The First Hospital of Lanzhou University (ldyyyn-2018-16).